Estrutura genética e relações de parentesco no mico leão preto (Leontopithecus chrysopygus) inferidos por marcadores microssatélites - Javarotti, Nathalia Bulhões (Universidade Federal de São Carlos, 2021)
Ex situ breeding and conservation programs have been established for endangered species with the objective of keeping populations self-sustainable and demographically stable, capable of to retain genetic diversity and avoid inbreeding depression. However, despite the success of In many of these programs, maintaining a species in captivity faces major challenges. The low number of individuals that originates the founding group and the reproduction between individuals related factors lead to the loss of genetic diversity and the increase of inbreeding in captive populations. To address these issues, some conservation programs have started to combine traditional analyzes, based on the genealogical records of the species (Studbook), with genetic-molecular approaches. This information can be used even to integrated in situ and ex situ management, which facilitates decision-making that translocations and / or the creation of priority conservation areas, and, eventually, introductions of captive animals in the wild. In this context, the present work analyzed the diversity genetics of free-living and captive groups of the black lion tamarin Leontopithecus chrysopygus, a species of endangered primate, endemic to the Atlantic Forest of São Paulo, which has been kept in captivity as an alternative strategy for their conservation, through markers microsatellites. The data demonstrate that captive management is succeeding in avoid homozygosis, since the Ho values ​​have also remained higher than those of the He after nine generations. The values ​​of Fis, He, Ho did not show significant differences between 2014 and 2018, however, there was a significant decrease in allelic wealth in Brazilian groups, demonstrating that loss of alleles is occurring over the generations. Kinship analyzes for captive groups confirmed the relationships described in Studbook; and the genetic structuring analyzes demonstrated the existence of a captive ex situ metapopulation. As for the groups in situ, differences were evidenced significant differences in the levels of genetic diversity calculated for populations belonging to three distinct fragments. The values ​​observed for the inbreeding coefficient, however, were similar, showing an excess of heterozygote and probably a behavior flight tendency from inbreeding. The genetic structuring analyzes showed that the three free-living populations analyzed in this study are structured and have strong genetic differentiation. When the ex situ and in situ groups were compared, it was verified existence of population structure.
Genetic structure and kinship relationships in the black lion tamarin (Leontopithecus chrysopygus) inferred by microsatellite markers
Keywords: Diversidade genética; Conservation genetics; Genética da conservação; Leontopithecus chrysopygus; Mico-leão-preto; Black lion tamarin; Genetic diversity; CIENCIAS BIOLOGICAS::GENETICA